TRANSFORMATION OF FIQH KNOWLEDGE IN THE NASKAH TRADITION IN LUHAK AGAM MINANGKABAU (HISTORICAL STUDY APPROACH) - Nofra, Doni; Pratama, Fikri Surya (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2025)
The presence of Islam in Minangkabau had a significant impact on the formation of the intellectual tradition of the community, especially in the writing and transmission of religious knowledge. Islamic scholars, tarekat groups, and their students produced various religious manuscripts that played an important role in the education and social life of the Minangkabau people. This research aims to examine the process of fiqh knowledge transformation through local manuscripts in Agam Regency, West Sumatra. Using a qualitative approach and historical research method, data were collected through field observations, in-depth interviews, and literature studies. The analysis was conducted interactively since the beginning of data collection by emphasising the historical, social and cultural context of the manuscripts studied. The results show that the existence and distribution of fiqh manuscripts in the Luhak Agam region is a reflection of the distinctive Islamic intellectual dynamics in Minangkabau. The fiqh manuscripts from Agam contain various important themes, ranging from the fiqh of worship to socio-cultural issues, such as the pros and cons of Minangkabau customs, women's issues and other unique issues. These manuscripts were not only used in teaching in surau, but also became instruments in fighting for social transformation in society. Thus, fiqh manuscripts in Minangkabau reflect the dynamics of interaction between texts, education and the evolving social reality.